2010
DOI: 10.1590/s1519-566x2010000600027
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de infestación, colonización e infección de Triatoma dimidiata (Latreille) (Hemiptera: Reduviidae) en Campeche, México

Abstract: Indicators of Infestation, Colonization and Infection of Triatoma dimidiata (Latreille) (Hemiptera:Reduviidae) in Campeche, México ABSTRACT -Triatoma dimidiata (Latreille) is considered to be one of the primary vectors of Chagas disease in Southern Mexico and Central America. The objective of the present study was to obtain ecological information on T. dimidiata in two rural communities of Campeche, Mexico, where the vector is poorly studied. Our work consisted of monthly samplings carried out during one-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
7
0
4
Order By: Relevance
“…The months reporting higher capture, registering 66% (24/36), were those corresponding to the dry season (March-April). This is the only arthropod vector reported for the Campeche state, which seems to be more abundant during the dry season, as reported by Ruiz Piña and CruzReyes (2002) and Hernández et al (2010). Activities of both reservoirs coincide on the dry season.…”
Section: Resultssupporting
confidence: 60%
“…The months reporting higher capture, registering 66% (24/36), were those corresponding to the dry season (March-April). This is the only arthropod vector reported for the Campeche state, which seems to be more abundant during the dry season, as reported by Ruiz Piña and CruzReyes (2002) and Hernández et al (2010). Activities of both reservoirs coincide on the dry season.…”
Section: Resultssupporting
confidence: 60%
“…10 However, colonization was very low (less than 5%). These data may support the notion that T. dimidiata is rather a visiting vector than a domiciliated vector.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in this community indicated that intradomestic infestation in the months between April and June (months that correspond to hot and dry season) can reach up to 53%, and the infection index can reach 20%; however, the colonization index is below 5%. 10 The above data suggest that inhabitants of this community could be at risk of Trypanosoma cruzi infection and Chagas disease.…”
Section: Introductionmentioning
confidence: 85%
“…Las condiciones climáticas también inciden en el número de insectos capturados durante el año, el cual aumenta en las temporadas secas, que en Centroamérica corresponden a los meses de marzo y septiembre (68,69). En algunos estudios, se ha examinado la relación entre las variables climáticas y la presencia de T. dimidiata utilizando sistemas de información geográfica y los parámetros registrados en las estaciones.…”
Section: Factores Asociados Con La Presencia De Triatominos En Vivienunclassified